Strategies in increasing women’s participation in commodity value chain development: Experiences from IPMS - Aregu, Lemlem; Puskur, Ranjitha (International Livestock Research Institute, 2011)
Gender roles and relationships play determining roles in the production and marketing of agricultural commodities. However, the introduction of new technologies and practices, through improved service provision and market oriented growth often either disregards the gender consequences or many benefits bypass women including business development services such as training and credit. In some cases, due to commercialization women are unable to find their power in or right to control over women’s commodities they had before. This has implications not only for equity, but also may be detrimental to the long-term sustainability of commercialization. Considering this Improving Productivity and Market Success (IPMS3) project employed different strategies and approaches across its Pilot Learning Woredas to reach out many women in commodity development as possible. Therefore this paper is presented the different strategies and approaches employed to reach out women in commodity development through increasing women accesses to technologies, resources and; providing the required skill and knowledge to women.